Review of Experiences with Post-Conflict Needs Assessments 2008-2015 - Garrasi, Donata; Allen, Ross (World Bank, Washington, DC, 2016)
Since its introduction in 2003, the Post Conflict Needs Assessment (PCNA) methodology has been used by the European Union, United Nations, and World Bank to frame multi-lateral assessments in more than ten countries emerging from conflict. The commitment to undertake such joint assessments is enshrined in the 2008 Joint Declaration on Crisis and Post-Crisis Recovery Planning and Assessment, which formally commits the three partners to work together on planning and implementing support to countries suffering from crisis. The current review takes stock of these experiences, and offers insights into the process, methodology and approach to such assessments in response to conflict. It offers valuable insights into the rationale behind joint assessments in conflict-contexts, and puts forward recommendations for how the assessment methodology and partnership between the three organizations can be further strengthened to support effective recovery and peacebuilding.